SOLUTION OF BINARY QUADRATIC DIOPHANTINEEQUATION: y2 = 63x2 +37 - DR. SHREEMATHI ADIGA*; SANJANA; DHANYA; NISHA; PRATHIBHA (International Journal of Mathematical Archive, 2026)
In this paper, the binaryquadratic equation y2=63x2+37, which representsa hyperbola, also known as positive form of Pell equation is analyzed for finding its non-zero distinct integer solutions. Knowing an integral solution of the given hyperbola, integer solutions for other choices of hyperbolas and parabolas are presented. A few relations between the solutions are presented, Using the solutions, a special Pythagorean triangle is constructed.